Methane emissions from riverine ecosystems in the Yangtze River basin are driven by ebullition rather than diffusion - Xiuyuan Chen; Fuhong Sun; Jiayue Li; Ziteng Wang; Yiding Guo; Nannan Huang; Qianyu Zhao; Fengchang Wu (Communications Earth & Environment)
Abstract Quantifying methane emissions from riverine ecosystems is crucial for optimizing greenhouse gas control strategies. However, partitioning methane emissions between diffusion and ebullition pathways remains insufficiently investigated. Here, we developed data-driven models to separately quantify diffusive and ebullitive methane fluxes and characterized the spatiotemporal distribution of methane dynamics from rivers within the Yangtze River Basin, China. Annual methane emissions emitted from rivers across the Yangtze River Basin were estimated at 0.827 (0.751–0.903) teragrams, with ebullition dominating total emissions (accounting for 86%). Seasonal methane emissions exhibited a pattern of being higher in summer and lower in winter, while dissolved methane concentrations were higher in autumn and winter than in spring and summer. Urban rivers exhibited significantly higher methane concentrations, diffusive fluxes, and ebullitive fluxes than natural rivers. This study provides valuable insights for refining methane prediction models and highlights the critical contribution of ebullition to methane emissions from large-scale river systems.